ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PENYELESAIAN PADA PROYEK PEMBANGUNAN APARTEMEN URBAN SIGNATURE CIRACAS - Rizky Tasya Putri; Setia Damayanti; Akhmad Dofir (Construction and Material Journal, 2023)
The delay in completion of construction that has exceeded the work time target according to the initial agreement is very powerful on the construction project itself. Delays in the project occur due to problems that arise in terms of materials, labor, costs, equipment, environment, and others. In this research, an analysis was carried out on what factors were the cause of the delay in the completion of the superstructure and the rating of the value of the reliability function of each work. The Fault Tree Analysis (FTA) approach would be employed, which is a method that makes use of fault tree analysis in the form of a graphic model based on the outcomes of conducted interviews. In the graphic model, there were several event symbols and logic gate symbols to connect the event symbols. On the graphic model, the simplest cut set was acquired using Boolean algebra and the Method of Obtain Cut Set (MOCUS). Based on the results of the analysis, there were 33 basic events or jobs that experienced delays, including changes in rebar supply by the Owner, limited human resources, a lot of repair work, evaluation of the project schedule, SILO SIO PH licensing, late payments, delays in material delivery, and others. Typical structural work and ladder structures, the Boolean algebra law can be applied because it has a repeating code. Meanwhile, on the roof of the engine room, the law of algebra cannot be applied since the work does not have a repeating code. The reliability function is calculated in the analysis that follows. When all three variables are accurate, the system operates as intended.